The Sculptural Decoration of Public Buildings and the Second Sophistic: Side as an Example - Reimann, Manuel (Istanbuler Mitteilungen, 2024)
The preserved statues from Side, which were created in Roman imperial times, are among the outstanding examples of Roman-era plastic art from Asia Minor. The majority of these sculptures were created in the 2nd and 3rd centuries A.D., but were replicas of iconographic types which in turn date to the so-called Classical Greek and Hellenistic eras. Based on the sculptural decor of the Theater and the so-called Building M in Side, the paper discusses the extent to which the cultural movement of the Second Sophistic manifested itself in the sculptural environment of public buildings in Side, with comparative examples from other cities of Asia Minor also being cited. Various aspects of the Second Sophistic can be recognized in this way and allow further understandings concerning the processes that contributed to the particular choice of the statue types and iconographical subjects used. The aim is to gain a wider view of the sculptural environment in public spaces in Side.